HIJRAH DALAM KONTEKS MASA KE MASA: DARI AYAT MAKKIYAH, AYAT MADANIYYAH HINGGA KONTEKS MASA SEKARANG - Taufiq Ikram Ash Syidiqi (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to analyze the meaning of the term hijrah in the Qur’an by tracing its semantic development from the period of Makkiyah verses, Madaniyyah verses, to its interpretation in the modern context. In Islamic scholarship, hijrah is not merely a physical migration, as exemplified by the Prophet Muhammad’s migration from Makkah to Madinah, but also represents moral, spiritual, and social transformation toward a better life. This research employs a normative-theological approach combined with linguistic and thematic exegesis analysis to explore the meaning of hijrah based on the historical context of revelation and its contemporary relevance. The findings reveal that in Makkiyah verses, such as Surah Al-Mudatsir (74:5), hijrah emphasizes a spiritual dimension, referring to the abandonment of sin and polytheism in favor of faith and purity. In contrast, Madaniyyah verses, such as Surah Al-Baqarah (2:218), portray hijrah as a physical act of migration for the sake of defending and spreading Islam. In the modern era, hijrah has evolved into a moral and symbolic concept reflecting one’s effort to transform behavior, lifestyle, and spirituality according to Islamic values. Therefore, this study concludes that hijrah is a dynamic concept that continuously adapts to temporal and social contexts while maintaining its core essence of transformation and devotion as taught in the Qur’an.